MODEL KOMUNIKASI TERAPEUTIK DALAM PENDAMPINGAN ANAK KORBAN KEKERASAN DI P2TP2A PROVINSI ACEH - Nailul Husna (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
The purpose of this study was to analyze the implementation of stages in therapeutic communication for accompanying children who are victims of violence in P2TP2A Aceh Province, as well as to examine the factors that encourage and impede it and to identify a therapeutic communication model. This study employs a qualitative methodology using a case study approach. Interviews, observations, and documentation studies were used to gather data. Two psychologists, two counselors, a case manager, and a paralegal served as research informants. The findings of this study indicate that there are many phases in the therapeutic communication process when working with children who have experienced violence: the pre-interaction, introduction, work, and termination stages. Obstacles in the counseling room and the psychological state of psychologists/counselors and children who are victims of violence are the inhibiting factors for therapeutic communication, whereas supportive factors include the attitude of psychologists and counselors, their competence, the attitude of children who are victims of violence, social support, and socio-cultural background.